A novel orally active HDAC6 inhibitor T-518 shows a therapeutic potential for Alzheimer’s disease and tauopathy in mice - Tomohiro Onishi (Nature Portfolio, 2021)
Abstract Accumulation of tau protein is a key pathology of age-related neurodegenerative diseases such as Alzheimer's disease and progressive supranuclear palsy. Those diseases are collectively termed tauopathies. Tau pathology is associated with axonal degeneration because tau binds to microtubules (MTs), a component of axon and regulates their stability. The acetylation state of MTs contributes to stability and histone deacetylase 6 (HDAC6) is a major regulator of MT acetylation status, suggesting that pharmacological HDAC6 inhibition could improve axonal function and may slow the progression of tauopathy. Here we characterize N-[(1R,2R)-2-{3-[5-(difluoromethyl)-1,3,4-oxadiazol-2-yl]-5-oxo-5H,6H,7H-pyrrolo[3,4-b]pyridin-6-yl}cyclohexyl]-2,2,3,3,3-pentafluoropropanamide (T-518), a novel, potent, highly selective HDAC6 inhibitor with clinically favorable pharmacodynamics. T-518 shows potent inhibitory activity against HDAC6 and superior selectivity over other HDACs compared with the known HDAC6 inhibitors in the enzyme and cellular assays. T-518 showed brain penetration in an oral dose and blocked HDAC6-dependent tubulin deacetylation at Lys40 in mouse hippocampus. A 2-week treatment restored impaired axonal transport and novel object recognition in the P301S tau Tg mouse, tauopathy model, while a 3-month treatment also decreased RIPA-insoluble tau accumulation. Pharmaceutical inhibition of HDAC6 is a potential therapeutic strategy for tauopathy, and T-518 is a particularly promising drug candidate.